2013
DOI: 10.1136/bjsports-2012-092063
|View full text |Cite
|
Sign up to set email alerts
|

Acromiohumeral distance measurement in rotator cuff tendinopathy: is there a reliable, clinically applicable method? A systematic review

Abstract: The results support the reliability of ultrasound and CT or MRI for the measurement of AHD; however, more studies in symptomatic populations are required. The reliability of AHD measurement using radiographs has not been supported by the studies reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
94
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 38 publications
(118 reference statements)
3
94
0
2
Order By: Relevance
“…Ranges of AHD are reported between 6mm and 16mm in healthy individuals [21,22]. Studies using the RTUS method to measure this distance have recorded values ranging between 5.6mm and 13.4mm [6,[23][24][25][26][27][28]. These findings are similar to this study measurements, which ranged between 5mm and 14mm.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Ranges of AHD are reported between 6mm and 16mm in healthy individuals [21,22]. Studies using the RTUS method to measure this distance have recorded values ranging between 5.6mm and 13.4mm [6,[23][24][25][26][27][28]. These findings are similar to this study measurements, which ranged between 5mm and 14mm.…”
Section: Discussionsupporting
confidence: 82%
“…It is necessary to determine whether the measurement really represents what is being measured: therefore, evaluating the reliability of the ultrasound is important, since such reliability indicates the extent to which scores for a subject sample can be reproduced in the same participants in subsequent tests [6]. In the main, ICC values reflected good to excellent reliability, suggesting that the use of RTUS to determine the resting position in the humeral head in varying arm positions is reliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review study also suggested that the ultrasonographic measurement of AHD is closely aligned with the measurements using radiograph, magnetic resonance imaging (MRI), and computed tomography. 19 The reliability of AHD measurement by ultrasound has been assessed in many studies. For example, excellent intra-rater reliability (0.87-0.94) and moderate-toexcellent inter-rater reliability (0.64-0.92) of the AHD have been demonstrated using ultrasound in ablebodied individuals with healthy and impinged shoulders.…”
Section: Introductionmentioning
confidence: 99%
“…It has also previously been shown that sonography is the most reliable method of measuring the acromiohumeral distance. 8 Different studies have used different methods to measure the acromiohumeral distance. The measurement between the acromium and the humeral head seems to be the most popular 4 ; however there was still variation in the measurement points.…”
mentioning
confidence: 99%